Microdisk electrode voltammetry: Theoretical characterization and experimental verification of a novel electrocatalytic mechanism - Brookes, B; Lawrence, N; Compton, R (2000)
A numerical method is used to characterize the steady-state voltammetry at microdisk electrodes of a new electrocatalytic reaction. This reaction, which occurs for the oxidation of MW-dimethylphenylenediamine (DMPD, A) in the presence of H2S (X) is believed to proceed via the following route: A -2e- B, B + X → B-X (k2), B-X -2e- [B-X]2+. Due to the presence of a reagent restricted homogeneous kinetic step, the reaction is labeled EC2xE. The numerical method for simulating this reaction scheme is based on the finite-difference formulation of coupled mass transport and kinetic equations in oblate spherical coordinates. The method is illustrated for not only the EC2xE but also the EC' reaction and is applicable to the simulation of steady-state limiting currents at microdisk electrodes. Iterative solutions are calculated using a GaussNewton scheme to overcome nonlinear homogeneous kinetic terms. The spatial convergence of the simulation for both reactions is investigated by considering the form of the concentration function describing the species. Via the comparison of working surfaces generated from simulated results, measuring the steady-state limiting current is shown to be insensitive to the resolution of EC', ECE, and EC2xE reactions. Experimental steadystate limiting current data is reported for the DMPD/FkS system at microelectrodes of 7.3, 19.5, and 25.0 //m diameter to verify the theory behind the EC2xE reaction. These results are shown to closely fit experimental data using a working surface interpolation method. Specifically, this method correctly predicts the variation of the steady-state limiting current with the concentration of FS for a 19.5 />m diameter microelectrode to a relative standard deviation of 1.9%. Similar analysis for the 7.3 and 25.0 fim electrodes results in a mean value of 1.4 × 107 mol-1 cm3 s-1 for the rate constant k2 in the DMPD/H2S system. © 2000 American Chemical Society.